Kourion Urban Space Project: Preliminary Report of the 2018 Season - Grimsley, Lucas; Davies, Thomas W.; Davey, Christopher J.; Weir Jr., William J. (Buried History: The Journal of the Australian Institute of Archaeology, 2024)
The 2018 season of the Kourion Urban Space Project (KUSP) continued the excavation of Building 4, a large structure situated just to the southwest of the Earthquake House on the Kourion promontory. Focusing on tracing the architecture of this building, this season revealed the northwest perimeter wall and identified two internal rooms: the courtyard and Room 35. Building 4 continues to yield high quality and imported artifacts including glass vessels and fragments of marble statuary along with imported marble and stone construction materials. These artifacts combined with the overall large size of this structure and construction materials suggest that this building served the elite class at Kourion, though it is still uncertain if it served a public or private purpose. This report was lodged with the Department of Antiquities, Cyprus, in January 2022 and is published here with the authors’ affiliations as they were at the time of the excavation.